2017
DOI: 10.1093/europace/eux233
|View full text |Cite
|
Sign up to set email alerts
|

Complications of pulmonary vein isolation in atrial fibrillation: predictors and comparison between four different ablation techniques: Results from the MIddelheim PVI-registry

Abstract: Overall complication rate of PVI with various techniques is 10.5%. Permanent deficit occurred only after PVAC and CPVI in 0.7% of patients. Female sex and a higher CHA2DS2-VASc score increase, while PVAC and CB-PVI decrease, overall risk. Differences in overall safety and individual complication profile make selection of the ablation technique in relation to clinical risk profile possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 21 publications
2
68
0
3
Order By: Relevance
“…This might be a result of the fact, that experienced operators performed more complex procedures. Female sex was not associated with higher complication rates as it is described in the literature [16][17][18][19][20][21]. This could be partly explained by a relatively small ablation cohort and a low number of complications.…”
Section: Complicationsmentioning
confidence: 47%
See 1 more Smart Citation
“…This might be a result of the fact, that experienced operators performed more complex procedures. Female sex was not associated with higher complication rates as it is described in the literature [16][17][18][19][20][21]. This could be partly explained by a relatively small ablation cohort and a low number of complications.…”
Section: Complicationsmentioning
confidence: 47%
“…Neither was a higher CHA2DS2-VASc Score associated with higher complication rate. CHA2DS2-VASc score and early institutional experience showed a higher complication rate in the literature [19][20][21][22]. This was also attributed to the small sample size and low complication rate.…”
Section: Complicationsmentioning
confidence: 94%
“…In this context, the involvement of greater areas in the ablation maybe important in the case of ATs originating alongside the PVs like in the present report. Furthermore, a large register study showed that the complication rates with CB ablation are lower than those with point‐per‐point RF ablation . The ability to perform ablation with the CB as a “single‐shot” device without the needing of more than one transseptal puncture in patients with an unusual left atrial anatomy is an additional argument for performing this ablation procedure empirically in CB technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous, mostly small studies on the second-generation PVAC GOLD catheter reported major complications ranging from 0 to 6.5% [6][7][8]15]. More recent and larger studies by Spitzer et al and De Greef et al showed more comparable major complication rates below 2% [15,18].…”
Section: Safety Outcomesmentioning
confidence: 91%